Preservative free travoprost and timolol fixed combination in the initial treatment of primary glaucoma: an assessment of hypotensive efficiency and safety - S. Yu. Petrov; L. V. Yakubova; L. V. Vasilenkova; O. M. Filippova; A. N. Zhuravleva; V. I. Kotelin (Российский офтальмологический журнал, 2022)
Purpose. To evaluate the efficacy and safety of Travapress Duo with respect to hypotensive results, changes in functional parameters, and adverse reactions. Material and methods. 30 patients aged 65–75 (averagely 71.3 ± 3.2 years) with a newly diagnosed primary open-angle glaucoma (POAG) received Travapress Duo in the evening, once a day. Goldman tonometry was performed during the screening, then 1 week, 1 month and 3 months from the treatment start. Static perimetry and optical coherence tomography (OCT) were performed before treatment and at the end of the 3rd month since the treatment start. Adverse events were recorded at each stage of the study.Results. As a result of a 3 month long therapy with Travapress Duo, a significant decrease in IOP was noted starting from the 1st week of instillations (by 34 %), after 1 month, by 35 % and after 3 months of observation by 36 %. By the end of the 3rd month of treatment, we noted an insignificant increase in visual acuity, a positive dynamic of the standard deviation and the standard deviation pattern, as well as OCT indicators, such as average thickness of the layer of retinal nerve fibers and the layer of retinal ganglion cells in the macula, stabilization of the thickness of the retinal ganglion cell complex layer and the size of the inner plexiform layer. One patient complained of discomfort and hyperemia by the end of the 1st week of drug instillation. No systemic side effects were noted during the follow-up, and in no case drug withdrawal was require. Conclusion. The preservative-free Travapress Duo drug displayed a high hypotensive efficacy, reducing the IOP to 36% of the initial value. The hypotensive effect was accompanied by indirect neuroprotection, which manifested itself in the positive changes observable in the results of functional studies with varying degrees of reliability. Travapress Duo is characterized by a low level of local side effects and can be recommended for both for the initial and long-term therapy of primary glaucoma of developed and advanced stages.